Prognostic value of neutrophil-to-lymphocyte ratio in patients with non–muscle-invasive bladder cancer with intravesical Bacillus Calmette–Guérin immunotherapy: a systematic review and meta-analysis - Huang, Jiaguo; Lin, Li; Mao, Dikai; Hua, Runmiao; Guan, Feifei (Frontiers in Immunology, 2024)
Background The predictive accuracy of the preoperative neutrophil-to-lymphocyte ratio (NLR) on the prognosis of patients with non-muscle-invasive bladder cancer (NMIBC) with intravesical Bacillus Calmette–Guérin immunotherapy (BCG) after transurethral resection of the bladder tumor (TURBT) remains unknown. Therefore, the current study performed a systematic review and meta-analysis to examine the relationship between preoperative NLR and the prognosis of patients with NMIBC with intravesical BCG immunotherapy. Methods For this systematic review and meta-analysis, articles were retrieved from PubMed, Cochrane Library, Web of Science, and Embase databases from their inception to 14 May 2024. The role of NLR in predicting recurrence and progression in NMIBC was determined using pooled hazard ratios (HRs) and 95% confidence intervals (CIs). Results Seven articles were included in this meta-analysis, involving 4,187 patients. An elevated NLR was significantly associated with recurrence (HR = 2.67, 95% CI = 1.34–5.32, P < 0.001) and progression (HR = 1.72, 95% CI = 1.13–2.60, P = 0.004) in patients with NMIBC with intravesical BCG immunotherapy. Conclusion This meta-analysis demonstrated that elevated preoperative NLR levels were significantly associated with recurrence and disease progression in patients with NMIBC who underwent intravesical BCG immunotherapy after TURBT. Systematic review registration https://inplasy.com/inplasy-2024-7-0058/, identifier 202470058.